Instant America - Mitchum, Robert; Martin Sandler Productions (Washington, DC : PBS Video, 1987)
Describes the new breed of entrepreneurs in today's electronic age. Focusses on television broadcasting.
Copy available in DVD format.
Keywords: Television broadcasting -- United States; Entrepreneurship -- United States